The formulation of lubricating grease from waste cooking oil - Muhammad Auni, Hairunnaja (2024)
Nowadays, the substantial amount of waste cooking oil (WCO) has been discarded away in improper manners until might affects to the environmental issues. This is due to the lack of awareness among people about the beneficial of reutilizing the WCO into new secondary products. Plus, in order to tackle these issues, a formulation process was made to turn WCO into lubricating grease by utilizing specific soap and non-soap thickeners (e.g. sodium stearate and fumed silica) and additives (e.g. Molybdenum disulphide (MoS2) and graphite). Although some studies were done by converting WCO into the grease products, there were lack of some parameters available to recognize the complete set of grease performance itself when using different thickener and additives. Hence, the purpose of this research was to formulate the lubricating grease from WCO using sodium stearate and F.S. as thickeners within and without the incorporation of additives, and to test the greases properties according to ASTM (American Standard Testing Method). The early stage of formulation began by having an oil treatment via filtrating (removes undesired impurities) and heating above 100℃ (removes moisture content). At first, the formulated greases without additive were divided into two categories sodium grease and F.S. grease. The formulation began by heating WCO at 90℃ for fumed silica grease and 180℃ for sodium grease prior the homogenization within the thickeners. Then, the greases will be further cooled for several days when the mixture had turned into gel likepaste structure. Thus, they will be tested via ASTM analysis for selecting the best formulated greases. Next, the new reformulated greases will be produced within the incorporation of the additives. The reformulated grease will be further tested via ASTM analysis including tribology analysis until the superior reformulated grease was chosen. Therefore, the best selected grease fell on fumed silica grease with MoS2 (F.G88M) for non-soap grease and sodium grease with MoS2 (SG58M) for soap grease at 88% and 58% WCO content respectively. Both of them had 2-3 of NLGI value under consistency test, null oil separation value, 11.9372% (at ambient) and 6.9463% (at 70℃) of oil bleeding values for SG58M, 9.2964% (at ambient) and 5.6473% (at 70℃) of oil bleeding values for F.G88M, 222.33 and >350 of dropping point value for SG58M and F.G88M, and classification of corrosion at 1a and 1b for SG58M and F.G88M respectively. However, the coefficient of friction (COF) and wear scar diameter (WSD) value of SG58M were 0.0253 and 467µm. Meanwhile, the COF and WSD value of F.G88M were 0.0017 and µm, giving an indication that these parameters affected most interesting things which make both of them eligible to be selected as the best formulated greases of different categories. The lower the COF and WSD value, the higher the grease’s quality. In summary, the qualities of greases made from WCO are good and similar to industrial standards, and the addition of additives to the formulation of the grease affects its tribological properties.